Dynamics of the regulation of Hsp90 by the co‐chaperone Sti1 - Lee, Chung-Tien; Graf, Christian; Richter, Sebastian; Mayer, Matthias P. (The EMBO journal, 2012)
In eukaryotic cells, Hsp90 chaperones assist late folding steps of many regulatory protein clients by a complex ATPase cycle. Binding of clients to Hsp90 requires prior interaction with Hsp70 and a transfer reaction that is mediated by the co‐chaperone Sti1/Hop. Sti1 furthers client transfer by inhibiting Hsp90's ATPase activity. To better understand how Sti1 prepares Hsp90 for client acceptance, we characterized the interacting domains and analysed how Hsp90 and Sti1 mutually influence their conformational dynamics using hydrogen exchange mass spectrometry. Sti1 stabilizes several regions in all three domains of Hsp90 and slows down dissociation of the Hsp90 dimer. Our data suggest that Sti1 inhibits Hsp90's ATPase activity by preventing N‐terminal dimerization and docking of the N‐terminal domain with the middle domain. Using crosslinking and mass spectrometry we identified Sti1 segments, which are in close vicinity of the N‐terminal domain of Hsp90. We found that the length of the linker between C‐terminal dimerization domain and the C‐terminal MEEVD motif is important for Sti1 association rates and propose a kinetic model for Sti1 binding to Hsp90.
Gesehen am 02.05.2018